Kajian Etnomatematika pada Aktifitas Tengkulak dalam Sistem Tebas Padi Petani di Desa Suboh Situbondo - Zainul Munawwir; Lisma Dian Kartika Sari; Fredi Yatmo Dwi Harjo; Anisyah Aulia Masruro (STKIP PGRI SITUBONDO, 2023)
As the rice harvest approaches, most of the farmers in Suboh Village, Suboh District, and Situbondo Regency are still very dependent on the slashing system by middlemen. However, there is something that makes researchers interested, namely when middlemen carry out calculations to determine price bids to farmers with special tricks. Researchers believe that these activities are full of mathematical concepts that the middlemen themselves may or may not be aware of. The purpose of this study is to examine the relationship between mathematics and culture, especially in the activities of middlemen in the farmer's rice harvest slash system. This research is classified as qualitative research with an ethnographic research design. The research subjects in this study were 3 middlemen who were selected by purposive sampling area and used to buy agricultural commodities from rice farmers using the slashing system in the fields. The data in this study are data taken or collected directly by researchers from research subjects/informants, including observation data and (semi-structured) interview data. Data analysis techniques go through the stages of data reduction, data presentation, conclusion, and verification. The results showed that there were some fundamental mathematical activities carried out by middlemen, namely measuring, designing, locating, playing, counting, and explaining. While the mathematical concepts seen in this activity include the concepts of length and width, the area of ​​a rectangle, arithmetic sequences and series, profit and loss, and logic.